Community-Based Service-Learning Model as a Strategy for Developing Mutual Cooperation Character in Elementary Schools - Sama; Asmoni (Universitas Pendidikan Ganesha, 2025)
Developing the character of cooperation in elementary schools is one of the main challenges in education in Indonesia. The community-based service-learning learning model is expected to be a solution to improve these social values in students. This study aims to test the effectiveness of the community-based service-learning learning model in developing the character of cooperation in grade 5 elementary school students. The method used is Research and Development with the ADDIE approach. The instruments used include questionnaires and observations to measure changes in student attitudes, and the data are analyzed quantitatively. The results showed a significant increase in each indicator measured: group cooperation, concern for friends, and participation in social activities. The average questionnaire score increased from 4.5 (pre-intervention) to 4.7 (post-intervention), and observations showed an average increase from 52.5% (pre-intervention) to 85% (post-intervention). The implications of this study indicate that the community-based service-learning model effectively strengthens students' cooperation character and can be applied more widely in elementary schools as part of character education to form students who are more caring and cooperative in social life.